Dynotest Design Analysis for Electrical Converted Vehicles - Danardono Agus Sumarsono; Fuad Zainuri; Muhammad Hidayat Tullah; Rahmat Noval; Sonki Prasetya; Rahmat Subarkah; Tia Rahmiati; Widiyatmoko widi; Muhammad Ridwan (MBI, 2023)
The study comprises dynotest design and analysis to measure torque and horsepower. Basically, a dynotest carried out by apply certain load to the axle of a combustion motor through the braking mechanism of its crankshaft. Due to the high price of a Dynotest unit in the market, it is relatively difficult for a developing institution to own it on their site. The study target to design a simple and good accurate Dynotest within a reasonable price. The study used a common standard method for design analysis which rely on function and structural approach. Functionally, Dynotest is designed to be used to an ouput of an electical motor. Loading on motor shaft was done by disc brake braking mechanism. Structurally, Dynotest was designed to use rollers. As a main component, its mounting construction is connected to a motor to generate electrical power. Power transmitted from the motor to Dynotest through a center joint shaft, torque measured by load cell while the rotation of shaft itself counted by a digital tachometer. Test result show that electricity was produced from the simple construction and Dynotest functioned well in measuring it. Measurement data of roller support shaft performance showed a motor torque performance curve which are similar with the typical of similar Dynotest. Construction Test done by applying Solid Work software analysis to some components partially on rollers and on the construction assembly as a whole unit